Optical laminate and image display device

By performing surface modification treatment and optimizing the adhesive ratio in the laminated structure of the optical laminated body, the problem of difficulty in peeling off the optical laminated body during the manufacturing process is solved, and high reoperability and higher manufacturing efficiency are achieved.

CN119790333APending Publication Date: 2025-04-08NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380064992.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-18
Filing Date
2023-11-15
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, the optical laminate is difficult to effectively peel off during the manufacturing process, resulting in poor reoperability.

Method used

In the laminated structure in the optical laminate, the surface modification process is performed between the first adhesive sheet and the second optical film, and a specific adhesion and adhesion ratio are satisfied to improve the reoperability of the optical laminate.

Benefits of technology

High reoperability of the optical laminate is achieved, allowing it to be peeled off from the adherend more easily, and manufacturing efficiency and product performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790333A_ABST
    Figure CN119790333A_ABST
Patent Text Reader

Abstract

Provided is an optical laminate in which a first optical film, a first adhesive sheet, a second optical film, and a second adhesive sheet are laminated in this order. The surface of the first adhesive sheet on which the second optical film is laminated has been surface-modified. When the adhesion force between the first adhesive sheet and the second optical film at 80 DEG C is defined as F1 (80 DEG C), and the initial adhesion force between the second adhesive sheet and the alkali-free glass at 80 DEG C when the second adhesive sheet is bonded to the alkali-free glass is defined as G0 (80 DEG C), the optical laminate satisfies F1 (80 DEG C) / G0 (80 DEG C) > = 2. The optical laminate is suitable for improving reworkability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body and an image display device. Background Art

[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) are rapidly becoming popular. The above-mentioned various image display devices usually have a laminated structure of an image forming layer such as a liquid crystal layer, an EL light-emitting layer, and an optical laminate, and the optical laminate comprises an optical film and an adhesive sheet. The adhesive sheet is mainly used for the bonding between the films contained in the optical laminate, and the bonding between the image forming layer and the optical laminate. Examples of optical films are polarizers, phase difference films, and polarizers with phase difference films formed by integrating polarizers and phase difference films.

[0003] Patent Document 1 describes a method for laminating an adhesive layer to a resin film, wherein the surfaces of the resin film and the adhesive layer to be laminated are subjected to surface activation treatment and then laminated.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-213314 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The image display device, for example, has a structure in which an optical laminate and an image forming layer are bonded via an adhesive sheet of the optical laminate. In addition, the optical laminate has an interlayer adhesive sheet, for example, disposed between a phase difference film and a polarizing film, while having the adhesive sheet. In the manufacture of such an image display device, it is sometimes required to peel off the optical laminate attached to an adherend from the adherend, which is called a re-operation. When peeling the optical laminate from the adherend, it can be considered to form a peeling portion by peeling off a portion of the end of the optical laminate from the adherend, and the optical laminate as a whole is peeled off from the adherend by grasping the peeling portion and stretching it. It should be noted that the peeling portion becomes the starting portion of the peeling of the entire optical laminate, that is, the starting point or starting point of the peeling, and therefore, it is sometimes referred to as the "starting point" below.

[0009] An object of the present invention is to provide an optical layered body having improved reworkability.

[0010] Solutions to the problem

[0011] The present invention provides an optical laminate, wherein a first optical film, a first adhesive sheet, a second optical film and a second adhesive sheet are laminated in sequence.

[0012] The surface of the first adhesive sheet on which the second optical film is laminated has been subjected to surface modification treatment.

[0013] When the adhesion between the first adhesive sheet and the second optical film at 80°C is defined as F1 (80°C), and the initial adhesion between the second adhesive sheet and the alkali-free glass at 80°C when the second adhesive sheet is bonded to the alkali-free glass is defined as G0 (80°C), the following formula (1) is satisfied:

[0014] F1(80℃) / G0(80℃)≥2 (1).

[0015] Furthermore, the present invention provides an image display device comprising the above-mentioned optical layered body and an image forming layer.

[0016] Effects of the Invention

[0017] According to the present invention, an optical layered body having improved reworkability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a cross-sectional view schematically showing an example of the optical layered body according to the present embodiment.

[0019] Figure 2 This is a schematic cross-sectional view showing another example of the optical layered body.

[0020] Figure 3 This is a schematic cross-sectional view showing an example of an optical layered body with a substrate.

[0021] Figure 4 This is a schematic cross-sectional view showing another example of the optical layered body with a substrate.

[0022] Figure 5 This is a schematic cross-sectional view showing another example of the optical layered body with a substrate.

[0023] Figure 6 This is a schematic cross-sectional view showing another example of the optical layered body with a substrate.

[0024] Figure 7 It is a schematic cross-sectional view showing an example of an image display device.

[0025] Figure 8 It is a cross-sectional view schematically showing another example of the image display device.

[0026] Fig. 9 This is a schematic cross-sectional view showing an example of an image display device after the starting point is created. DETAILED DESCRIPTION

[0027] The optical layered body of the first embodiment of the present invention is an optical layered body in which a first optical film, a first adhesive sheet, a second optical film, and a second adhesive sheet are laminated in this order.

[0028] The surface of the first adhesive sheet on which the second optical film is laminated has been subjected to surface modification treatment.

[0029] When the adhesion between the first adhesive sheet and the second optical film at 80°C is defined as F1 (80°C), and the initial adhesion between the second adhesive sheet and the alkali-free glass at 80°C when the second adhesive sheet is bonded to the alkali-free glass is defined as G0 (80°C), the following formula (1) is satisfied:

[0030] F1(80℃) / G0(80℃)≥2 (1).

[0031] In the second aspect of the present invention, for example, in the optical laminate of the first aspect, when the adhesion between the first adhesive sheet and the second optical film at 23°C is defined as F1 (23°C), and when the surface of the first adhesive sheet on which the second optical film is laminated is not subjected to surface modification treatment, the adhesion between the first adhesive sheet and the second optical film at 23°C is defined as F0 (23°C), the following formula (2) is satisfied:

[0032] F1(23℃) / F0(23℃)>1.30 (2).

[0033] In a third aspect of the present invention, for example, in the optical layered body of the first or second aspect, the surface modification treatment is a corona treatment.

[0034] In a fourth aspect of the present invention, for example, in the optical laminate according to any one of the first to third aspects, when the adhesion between the first adhesive sheet and the second optical film at 23°C is defined as F1 (23°C), and the initial adhesion between the second adhesive sheet and the alkali-free glass at 23°C when the second adhesive sheet is bonded to the alkali-free glass is defined as G0 (23°C), the following formula (3) is satisfied:

[0035] F1(23℃) / G0(23℃)≥1.2 (3).

[0036] In a fifth aspect of the present invention, for example, in the optical layered body according to any one of the first to fourth aspects, the thickness T2 of the second adhesive sheet is 8 μm or more.

[0037] In a sixth aspect of the present invention, for example, in the optical laminate according to any one of the first to fifth aspects, a thickness T2 of the second adhesive sheet and a thickness T1 of the first adhesive sheet satisfy T2 / T1≥1.1.

[0038] In a seventh aspect of the present invention, for example, in the optical layered body according to any one of the first to sixth aspects, the storage modulus G of the first adhesive sheet at 23° C. is A '(23°C) and the storage modulus G of the second adhesive sheet at 23°C B '(23℃) satisfies G A '(23℃) / G B '(23℃)≥1.1.

[0039] In the 8th aspect of the present invention, for example, in the optical layered body described in any one of the 1st to 7th aspects, when the second adhesive sheet is bonded to the alkali-free glass, the initial bonding strength between the second adhesive sheet and the alkali-free glass at 23°C is defined as G0 (23°C), and when the second adhesive sheet is bonded to the alkali-free glass and the bonding strength between the second adhesive sheet and the alkali-free glass at 23°C after 2 weeks is defined as G2 (23°C), G2 (23°C) / G0 (23°C) ≤ 1.5 is satisfied.

[0040] An image display device according to a ninth aspect of the present invention includes the optical layered body according to any one of the first to eighth aspects, and an image forming layer.

[0041] Hereinafter, embodiments of the present invention will be described with reference to the drawings. The present invention is not limited to the embodiments described below.

[0042] In the optical laminate of the present embodiment, a first optical film, a first adhesive sheet, a second optical film and a second adhesive sheet are sequentially laminated. The surface of the first adhesive sheet laminated with the second optical film is subjected to surface modification. The adhesion between the first adhesive sheet and the second optical film at 80°C is defined as F1 (80°C). When the second adhesive sheet is bonded to the alkali-free glass, the initial adhesion between the second adhesive sheet and the alkali-free glass at 80°C is defined as G0 (80°C). At this time, the optical laminate satisfies the following formula (1):

[0043] F1(80℃) / G0(80℃)≥2 (1).

[0044] Figure 1 1 is a cross-sectional view schematically showing an example of an optical laminate of the present embodiment. The optical laminate 10A includes a first optical film 1, a first adhesive sheet 2, a second optical film 3, and a second adhesive sheet 4. The optical laminate 10A has a structure in which the first optical film 1, the first adhesive sheet 2, the second optical film 3, and the second adhesive sheet 4 are laminated in this order.

[0045] The first optical film 1 is in contact with the first adhesive sheet 2. The first optical film 1 is disposed in contact with one main surface 2a of the first adhesive sheet 2. Figure 1 In the embodiment, the first optical film 1 is in contact with the entire main surface 2a of the first adhesive sheet. However, the first optical film 1 may be in contact with only a portion of the main surface 2a of the first adhesive sheet 2. In this specification, the "main surface" refers to the surface of a film or layer having the largest area.

[0046] The first adhesive sheet 2 is formed on the second optical film 3. The first adhesive sheet 2 is formed on one main surface 3a of the second optical film 3. Figure 1 In the embodiment, the first adhesive sheet 2 is formed on the entire one principal surface 3a of the second optical film 3. However, the first adhesive sheet 2 may be formed only on a part of the one principal surface 3a of the second optical film 3.

[0047] At least one of the surfaces selected from the first adhesive sheet 2 on which the second optical film 3 is laminated and the second optical film 3 on which the first adhesive sheet is laminated is subjected to a surface modification treatment. Thus, the adhesion between the first adhesive sheet 2 and the second optical film 3 can be improved. The details of the surface modification treatment will be described later.

[0048] The second adhesive sheet 4 is formed in contact with the second optical film 3. Specifically, the second adhesive sheet 4 is formed on the main surface 3b of the second optical film 3 opposite to the main surface 3a on which the first adhesive sheet 2 is formed. Figure 1 In the embodiment, the second adhesive sheet 4 is formed on the entire one principal surface 3 b of the second optical film 3 . However, the second adhesive sheet 4 may be formed only on a portion of the one principal surface 3 b of the second optical film 3 .

[0049] In the present embodiment, the value calculated by formula (1) can be 3.5 or more, or 4.0 or more, 4.5 or more, 5.0 or more, 6.0 or more, 8.0 or more, 9.0 or more, 9.1 or more, 9.3 or more, 9.5 or more, and further can be 10.0 or more. The upper limit of the value calculated by formula (1) can be 20.0 or 15.0.

[0050] (First Adhesive Sheet and Second Adhesive Sheet)

[0051] (First Adhesive Sheet)

[0052] The first adhesive sheet 2 has main surfaces 2a and 2b facing each other. The main surface 2a is opposite to the first optical film 1. The main surface 2a is the surface of the first adhesive sheet 2 on which the first optical film 1 is laminated. The main surface 2b is opposite to the second optical film 3. The main surface 2b is the surface of the first adhesive sheet 2 on which the second optical film 3 is laminated. The main surface 2a may have been subjected to a surface modification treatment. The main surface 2b has been subjected to a surface modification treatment. By subjecting the main surface 2b to a surface modification treatment, the above-mentioned adhesion F can be improved. The surface modification treatment may be applied to at least a portion of the main surfaces 2a and 2b of the first adhesive sheet 2. The surface modification treatment may be applied only to the ends of the main surfaces 2a and 2b of the first adhesive sheet 2, or may be applied to the main surfaces 2a and 2b as a whole. As surface modification treatment, corona treatment, plasma treatment, excimer treatment, flame treatment, etc. may be cited. It is preferred that the main surfaces 2a and 2b be subjected to a corona treatment as a surface modification treatment.

[0053] The conditions for the corona treatment of the main surface 2b are represented by the discharge amount, for example, 0.5 to 100 kJ / m 2 . The discharge capacity can be 1kJ / m 2 Above, 3kJ / m 2 Above, 7kJ / m 2 Above, further can be 9kJ / m 2 The upper limit of the discharge amount can be 70 kJ / m 2 、50kJ / m 2 、30kJ / m 2 、20kJ / m 2 , further can be 15kJ / m 2 If the discharge amount is too high, organic matter on the main surface 2b of the first adhesive sheet 2 may decompose to form a fragile layer, resulting in reduced adhesion. On the other hand, if the discharge amount is too low, the surface modification effect may not be obtained and the adhesion may not increase.

[0054] According to the research of the inventors, in the optical laminate, by performing surface modification treatment on the surface of the first adhesive sheet on which the second optical film is formed, there is a tendency that the adhesion F between the first adhesive sheet and the second optical film is improved. In addition, when the optical laminate is heated, there is a tendency that the adhesion F between the first adhesive sheet and the second optical film is further improved. According to the optical laminate 10A of the present embodiment, the surface of the first adhesive sheet 2 on which the second optical film 3 is laminated is subjected to surface modification treatment. Therefore, even if a starting point is made between the first adhesive sheet 2 and the second optical film 3 by interlayer peeling, the optical laminate 10A can be peeled off from the adherend.

[0055] The adhesion force F1 (80°C) is, for example, 10.0 N / 25 mm or more, and may be 12.0 N / 25 mm or more, 15.0 N / 25 mm or more, 20.0 N / 25 mm or more, 23.0 N / 25 mm or more, 23.5 N / 25 mm or more, 24.0 N / 25 mm or more, 25.0 N / 25 mm or more, 26.0 N / 25 mm or more, and may further be 26.5 N / 25 mm or more. The upper limit of the adhesion force F1 (80°C) is, for example, 30.0 N / 25 mm. It should be noted that the adhesion force F1 (80°C) refers to the adhesion force between the first adhesive sheet 2 and the second optical film 3 measured when the optical laminate with glass is placed on a hot plate set at 80°C and after 15 seconds. The method for measuring the adhesion force F (80°C) is described in the first embodiment.

[0056] Storage modulus G of the first adhesive sheet 2 at 23°C A The storage modulus G of the first adhesive sheet 2 at 23°C may be 0.01 MPa or more, 0.05 MPa or more, 0.08 MPa or more, 0.09 MPa or more, 0.10 MPa or more, 0.12 MPa or more, 0.15 MPa or more, 0.20 MPa or more, 0.5 MPa or more, and may further be 0.9 MPa or more. A The upper limit of '(23°C) is, for example, 3.0 MPa.

[0057] The thickness T1 of the first adhesive sheet 2 is, for example, 2 μm to 40 μm. The thickness T1 of the first adhesive sheet 2 may be 3 μm to 30 μm, 4 μm to 20 μm, 5 μm to 15 μm, or 8 μm to 15 μm.

[0058] The adhesion between the first adhesive sheet 2 and the second optical film 3 at 23°C is defined as adhesion F1 (23°C). On the other hand, the adhesion at 23°C when the surface of the first adhesive sheet on which the second optical film is formed is not subjected to surface modification treatment is defined as adhesion F0 (23°C). In this case, the following formula (2) can be satisfied:

[0059] F1(23℃) / F0(23℃)>1.30 (2).

[0060] The value represented by formula (2) may be 1.50 or more, 1.55 or more, 1.60 or more, 2.00 or more, 2.20 or more, 2.50 or more, or may be 3.00 or more. The upper limit of the value represented by formula (2) is, for example, 5.00.

[0061] The close fitting force F1 (23°C) is, for example, 5.0 N / 25 mm or more, 7.0 N / 25 mm or more, 8.0 N / 25 mm or more, 10.0 N / 25 mm or more, 14.0 N / 25 mm or more, 15.0 N / 25 mm or more, 16.0 N / 25 mm or more, 17.0 N / 25 mm or more, and further 20.0 N / 25 mm or more. The upper limit of the close fitting force F1 (23°C) is, for example, 30.0 N / 25 mm.

[0062] The close contact force F0 (23°C) is, for example, 5.0 N / 25 mm or more, 6.0 N / 25 mm or more, 7.0 N / 25 mm or more, 8.0 N / 25 mm or more, 9.0 N / 25 mm or more, 9.5 N / 25 mm or more, and further 10.0 N / 25 mm or more. The upper limit of the close contact force F0 (23°C) is, for example, 20.0 N / 25 mm.

[0063] (Second adhesive sheet)

[0064] The initial adhesive force G0 (80°C) is, for example, 0.1N / 25mm or more, 0.5N / 25mm or more, 1.0N / 25mm or more, 1.5N / 25mm or more, 2.0N / 25mm or more, 2.5 or more, and further 2.8N / 25mm or more. The upper limit of the initial adhesive force G0 (80°C) can be, for example, 6.0N / 25mm, 5.0N / 25mm, 4.0N / 25mm, or 3.5N / 25mm. In the determination of the initial adhesive force G0 (80°C), the second adhesive sheet 4 of the optical laminate 10A is first bonded to the alkali-free glass at 23°C, and then placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the second adhesive sheet 4 and the alkali-free glass. Thus, an optical laminate with glass is produced. Next, the optical laminate with glass is taken out of the autoclave, and after standing at 23°C for 20 minutes, the optical laminate with glass is immediately heated. The heating is performed by placing the optical laminate with glass on a hot plate set at 80°C for 15 seconds. The initial adhesive force G0 (80°C) is the adhesive force between the second adhesive sheet 4 and the alkali-free glass at 80°C obtained by measuring the optical laminate with glass immediately after heating the optical laminate with glass by the above method. The alkali-free glass is, for example, in the form of a plate and has a thickness of 0.5 mm or more.

[0065] Storage modulus G of the second adhesive sheet 4 at 23°C BThe storage modulus G of the second adhesive sheet 4 at 23°C may be 0.01 MPa or more, 0.05 MPa or more, 0.08 MPa or more, 0.09 MPa or more, 0.10 MPa or more, 0.12 MPa or more, or even 0.15 MPa or more. B The upper limit of '(23°C) is, for example, 0.5 MPa.

[0066] The initial bonding force between the second adhesive sheet 4 and the alkali-free glass at 23°C when the second adhesive sheet 4 is bonded to the alkali-free glass is defined as G0 (23°C). The initial bonding force G0 (23°C) is, for example, 8.0 N / 25 mm or less, 7.0 N / 25 mm or less, 6.0 N / 25 mm or less, 5.5 N / 25 mm or less, and further 5.0 N / 25 mm or less. The lower limit of the initial bonding force G0 (23°C) is, for example, 1.0 N / 25 mm. In the determination of the initial bonding force G0 (23°C), first, after bonding the second adhesive sheet 4 of the optical laminate 10A to the alkali-free glass at 23°C, the bonding between the second adhesive sheet 4 and the alkali-free glass is homogenized by placing the laminate in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes. An optical laminate with glass is thus produced. Next, the optical laminate with glass is taken out of the autoclave. The initial adhesive force G0 (23° C.) is the adhesive force between the second pressure-sensitive adhesive sheet 4 and the alkali-free glass at 23° C. measured when the optical laminate with glass is taken out of the autoclave and left to stand at 23° C. for 20 minutes.

[0067] Can make G A '(23℃) and G B '(23℃) satisfies G A '(23℃) / G B '(23°C)≥1.1. Thus, the reoperability can be further improved. A '(23℃) / G B G'(23°C) may be 2.0 or more, 3.0 or more, 4.0 or more, 5.0 or more, or 5.2 or more. A '(23℃) / G B The upper limit of '(23°C) is, for example, 8.0.

[0068] The optical laminate 10A may satisfy the following formula (3). The value represented by the formula (3) may be 1.5 or more, 1.7 or more, 2.0 or more, 2.5 or more, 3.0 or more, 3.5 or more, or further may be 4.0 or more. The upper limit of the value represented by the formula (3) is, for example, 7.0.

[0069] F1(23℃) / G0(23℃)≥1.2 (3)

[0070] Adhesive force G2 (23°C) refers to the adhesive force between the second adhesive sheet 4 of the optical laminate 10A and the alkali-free glass at 23°C after two weeks of bonding the second adhesive sheet 4 to the alkali-free glass. Adhesive force G2 (23°C) is, for example, 10.0N / 25mm or less, 8.0N / 25mm or less, 7.0N / 25mm or less, 6.0N / 25mm or less, 5.8N / 25mm or less, and further 5.2N / 25mm or less. The lower limit of adhesive force G2 (23°C) is, for example, 1.0N / 25mm. In the measurement of adhesive force G2 (23°C), first, after bonding the second adhesive sheet 4 of the optical laminate 10A to the alkali-free glass at 23°C, the bonding between the second adhesive sheet 4 and the alkali-free glass is homogenized by placing it in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes. Thus, an optical laminate with glass is produced. After the optical laminate with glass was prepared, it was left to stand at 23° C. and 55% RH. The adhesive force G2 (23° C.) is the adhesive force between the second adhesive sheet 4 and the alkali-free glass at 23° C. measured after two weeks in this state.

[0071] G0 (23 ° C) and G2 (23 ° C) can satisfy G2 (23 ° C) / G0 (23 ° C) ≤ 1.5. Sometimes, after the optical laminate is bonded to the adherend, the optical laminate is peeled off from the adherend after standing at room temperature for a few days to about 2 weeks. In addition, the adhesive sheet generally has the characteristic that the adhesive force gradually increases after being bonded to the adherend. The optical laminate 10A of the present embodiment, for example, satisfies G2 (23 ° C) / G0 (23 ° C) ≤ 1.5. Thus, even after a long time has passed after the optical laminate is bonded to the adherend such as the image forming layer, the reoperability can be further improved. G2 (23 ° C) / G0 (23 ° C) can be less than 1.3, and can also be less than 1.2. The lower limit of G2 (23 ° C) / G0 (23 ° C) is, for example, 1.0.

[0072] The thickness T2 of the second adhesive sheet 4 is, for example, 8 μm or more. The thickness T2 of the second adhesive sheet 4 may be 10 μm or more, 12 μm or more, 15 μm or more, or 18 μm or more. The upper limit of the thickness T2 of the second adhesive sheet 4 is, for example, 30 μm.

[0073] The thickness T2 of the second adhesive sheet 4 and the thickness T1 of the first adhesive sheet 2 can satisfy T2 / T1≥1.1. Thus, the reoperability can be further improved. T2 / T1 can be 1.2 or more, or 1.3 or more, 1.4 or more, 1.7 or more, 2.0 or more, and further can be 2.5 or more. The upper limit of T2 / T1 is, for example, 5.0.

[0074] The second adhesive sheet 4 has main surfaces 4a and 4b facing each other. The main surface 4a faces the second optical film 3. The main surface 4b is exposed outside the optical laminate 10A, for example, and is a surface on which an adherend such as glass is laminated. The main surface 4a of the second adhesive sheet 4 may be subjected to a surface modification treatment. The main surface 4b of the second adhesive sheet 4 may not be subjected to a surface modification treatment. The surface modification treatment described above for the first adhesive sheet 2 may be appropriately used.

[0075] [Adhesive composition (I)]

[0076] The first adhesive sheet 2 and the second adhesive sheet 4 are formed of, for example, an adhesive composition (I). The adhesive composition (I) is described in detail below. In the following description, the first adhesive sheet 2 and the second adhesive sheet 4 may be referred to as "adhesive sheets".

[0077] As the adhesive constituting the adhesive sheet, acrylic adhesive, rubber adhesive, vinyl alkyl ether adhesive, silicone adhesive, polyester adhesive, polyamide adhesive, urethane adhesive, fluorine adhesive, epoxy adhesive, polyether adhesive etc. can be cited. It should be noted that the adhesive constituting the adhesive sheet can be used alone or in combination of two or more. But from the aspects of transparency, processability, durability, adhesion, etc., it is preferred to use an acrylic adhesive (composition) containing a (meth) acrylic polymer alone. In other words, the adhesive sheet preferably includes a (meth) acrylic polymer. In this specification, "(meth) acrylic acid" refers to acrylic acid and methacrylic acid. In addition, "(meth) acrylate" refers to acrylate and methacrylate.

[0078] [(Meth)acrylic polymer (A)]

[0079] The (meth)acrylic polymer (A) may have a structural unit derived from a (meth)acrylic monomer having an alkyl group having 1 to 30 carbon atoms in a side chain as a main unit. The alkyl group may be linear or branched. The (meth)acrylic polymer (A) may have one or more structural units derived from a (meth)acrylic monomer (A1). Examples of the (meth)acrylic monomer (A1) are methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate and n-tetradecyl (meth)acrylate. In this specification, the term "main unit" refers to a unit that occupies, for example, 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, particularly preferably 80% by weight or more, and even more preferably 90% by weight or more of all structural units of a polymer.

[0080] The (meth)acrylic polymer (A) may have a structural unit derived from a (meth)acrylic monomer (A1) having a glass transition temperature (Tg) in the range of -70 to -20° C. when formed into a homopolymer. An example of the monomer (A1) is n-butyl acrylate.

[0081] The (meth)acrylic polymer (A) may have a structural unit other than the structural unit derived from the (meth)acrylic monomer (A1). The structural unit is derived from a monomer (A2) copolymerizable with the (meth)acrylic monomer (A1). The (meth)acrylic polymer (A) may have one or more of these structural units.

[0082] Examples of monomers (A2) are aromatic ring-containing monomers. The aromatic ring-containing monomers may be aromatic ring-containing (meth) acrylic monomers. Examples of aromatic ring-containing monomers are phenyl (meth) acrylate, phenoxyethyl (meth) acrylate, benzyl (meth) acrylate, phenoxydiethylene glycol (meth) acrylate, ethylene oxide-modified nonylphenol (meth) acrylate, hydroxyethylated β-naphthol (meth) acrylate, and biphenyl (meth) acrylate. The content of the structural unit from the aromatic ring-containing monomer in the (meth) acrylic polymer (A) is, for example, 0 to 50% by weight, 1 to 30% by weight, 5 to 25% by weight, 8 to 20% by weight, 10 to 18% by weight, and further 12 to 16% by weight. If the amount of the crosslinking agent (B) in the adhesive composition (I) is increased, a self-polymer of the crosslinking agent (B) may be formed. When the (meth) acrylic polymer (A) has a structural unit from an aromatic ring-containing monomer, the compatibility of the (meth) acrylic polymer (A) with the crosslinking agent (B) and its self-polymer may be improved. Improved compatibility can contribute to improved uniformity of the PSA sheet by, for example, suppressing precipitation from the polymer.

[0083] Other examples of monomer (A2) are hydroxyl-containing monomers. The hydroxyl-containing monomers may be hydroxyl-containing (meth)acrylic monomers. Examples of hydroxyl-containing monomers are hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate, and methyl (4-hydroxymethylcyclohexyl)acrylate.

[0084] When the first adhesive sheet 2 includes a (meth) acrylic polymer (A), and the (meth) acrylic polymer (A) has a structural unit derived from a hydroxyl-containing monomer, the content of the structural unit derived from the hydroxyl-containing monomer in the (meth) acrylic polymer (A) is, for example, 0.01% by weight or more, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.35% by weight or more, 0.4% by weight or more, and further 0.45% by weight or more. The content is 2% by weight or less, 1.5% by weight or less, 1.2% by weight or less, 1.0% by weight or less, 0.8% by weight or less, 0.7% by weight or less, or 0.6% by weight or less.

[0085] When the second adhesive sheet 4 includes a (meth)acrylic polymer (A), and the (meth)acrylic polymer (A) includes a structural unit derived from a hydroxyl-containing monomer, the content of the structural unit derived from the hydroxyl-containing monomer in the (meth)acrylic polymer (A) is, for example, 0.01% by weight or more, 0.05% by weight or more, 0.06% by weight or more, 0.07% by weight or more, 0.08% by weight or more, and further 0.09% by weight or more. The content is 1% by weight or less, 0.8% by weight or less, 0.5% by weight or less, 0.3% by weight or less, and 0.2% by weight or less.

[0086] Monomer (A2) may be a carboxyl group-containing monomer, an amino group-containing monomer, or an amide group-containing monomer. Examples of carboxyl group-containing monomers are (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of amino group-containing monomers are N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate. Examples of amide group-containing monomers include acrylamide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxymethyl-N-propyl(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine and N-(meth)acryloylpyrrolidine; and N-vinyl-containing lactam monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam. By making the (meth)acrylic polymer (A) have a structural unit derived from a carboxyl group-containing monomer, especially acrylic acid, the autopolymerization property of the crosslinking agent (B) can be improved, for example. The improvement of the autopolymerization property of the crosslinking agent (B) can be particularly helpful in suppressing the peeling of the adhesive sheet in a humidified environment and stabilizing the physical properties of the adhesive sheet in a system with a high content of the crosslinking agent (B).

[0087] Monomer (A2) may be a multifunctional monomer. Examples of multifunctional monomers include hexanediol di(meth)acrylate (1,6-hexanediol di(meth)acrylate), butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; and divinylbenzene. The multifunctional acrylate is preferably 1,6-hexanediol diacrylate and dipentaerythritol hexa(meth)acrylate.

[0088] The total content of the structural units derived from the carboxyl group-containing monomer, the amino group-containing monomer, the amide group-containing monomer and the multifunctional monomer in the (meth)acrylic polymer (A) is preferably 20% by weight or less, more preferably 10% by weight or less, and further preferably 8% by weight or less. When the (meth)acrylic polymer (A) has such structural units, the total content is, for example, 0.01% by weight or more, or 0.05% by weight or more. The (meth)acrylic polymer (A) may not contain structural units derived from multifunctional monomers.

[0089] Examples of other monomers (A2) are (meth)acrylate alkoxyalkyl esters such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate and 4-ethoxybutyl (meth)acrylate; epoxy group-containing monomers such as glycidyl (meth)acrylate and methylglycidyl (meth)acrylate; sulfonic acid group-containing monomers such as sodium vinyl sulfonate; phosphoric acid group-containing monomers; (meth)acrylates having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyltoluene; olefins such as ethylene, propylene, butadiene, isoprene and isobutylene, or dienes; vinyl ethers such as vinyl alkyl ether; and vinyl chloride.

[0090] The total content of the structural units derived from the other monomers (A2) in the (meth)acrylic polymer (A) is, for example, 30% by weight or less, 10% by weight or less, or 0% by weight (containing no such structural units).

[0091] The (meth) acrylic polymer (A) can be formed by polymerizing one or more of the above-mentioned monomers using a known method. Monomers and partial polymers of monomers can also be polymerized. The polymerization can be carried out, for example, by solution polymerization, emulsion polymerization, bulk polymerization, thermal polymerization, and active energy ray polymerization. Since an adhesive sheet with excellent optical transparency can be formed, solution polymerization and active energy ray polymerization are preferred. It is preferred to avoid contact between the monomer and / or partial polymer and oxygen during polymerization. For this purpose, polymerization in an inactive gas atmosphere such as nitrogen or polymerization in a state where oxygen is blocked by a resin film or the like can be used. The (meth) acrylic polymer (A) to be formed can be any form of a random copolymer, a block copolymer, a graft copolymer, etc.

[0092] The polymerization system for forming the (meth)acrylic polymer (A) may contain one or more polymerization initiators. The type of polymerization initiator may be selected according to the polymerization reaction, and may be, for example, a thermal polymerization initiator or a photopolymerization initiator.

[0093] The solvent used in the solution polymerization is, for example, esters such as ethyl acetate and n-butyl acetate; aromatic hydrocarbons such as toluene and benzene; aliphatic hydrocarbons such as n-hexane and n-heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone, but the solvent is not limited to the above examples. The solvent may be a mixed solvent of two or more solvents.

[0094] The polymerization initiator used in the solution polymerization is, for example, an azo polymerization initiator, a peroxide polymerization initiator, and a redox polymerization initiator. Peroxide polymerization initiators are, for example, dibenzoyl peroxide and tert-butyl permaleate. Among them, the azo polymerization initiator disclosed in Japanese Patent Publication No. 2002-69411 is preferred. The azo polymerization initiator is, for example, 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), but the polymerization initiator is not limited to the above examples. Relative to 100 parts by weight of the total amount of the monomer, the amount of the azo polymerization initiator is, for example, 0.05 to 0.5 parts by weight, and can also be 0.1 to 0.3 parts by weight.

[0095] The active energy rays used in the active energy ray polymerization are, for example, ionizing rays such as α rays, β rays, γ rays, neutron rays, electron rays, and ultraviolet rays. The active energy rays are preferably ultraviolet rays. Polymerization using ultraviolet irradiation is also called photopolymerization. The polymerization system of active energy ray polymerization typically includes a photopolymerization initiator. The polymerization conditions of the active energy polymerization are not limited as long as the (meth)acrylic polymer (A) can be formed.

[0096] Photopolymerization initiators include, for example, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketone photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators, but the photopolymerization initiators are not limited to the above examples.

[0097] Examples of benzoin ether photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of acetophenone photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketone photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. An example of a photoactive oxime photopolymerization initiator is 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl oxime). An example of a benzoin photopolymerization initiator is benzoin. An example of a benzyl photopolymerization initiator is benzyl. An example of a benzophenone photopolymerization initiator is benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenylketone. An example of a ketal photopolymerization initiator is benzyldimethylketal. An example of a thioxanthone photopolymerization initiator is thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.

[0098] The amount of the photopolymerization initiator used is, for example, 0.01 to 1 part by weight, or 0.05 to 0.5 part by weight, relative to 100 parts by weight of the total amount of the monomers.

[0099] The weight average molecular weight (Mw) of the (meth)acrylic polymer (A) is, for example, 1,000,000 to 2,800,000, and may be 1,200,000 or more, or further 1,400,000 or more, from the viewpoint of durability and heat resistance of the adhesive sheet. The weight average molecular weight (Mw) of polymers and oligomers in this specification is a value obtained by measurement based on GPC (gel permeation chromatography) (in terms of polystyrene).

[0100] The content of the (meth) acrylic polymer (A) in the adhesive composition (I) is, for example, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, or 85% by weight or more, in terms of solid content ratio. The upper limit of the content is, for example, 99.5% by weight, 99% by weight, 97% by weight, 95% by weight, 93% by weight, or 90% by weight.

[0101] [Crosslinking agent (B)]

[0102] The crosslinking agent (B) is typically a multifunctional crosslinking agent having two or more crosslinking reaction groups per molecule. The crosslinking agent (B) may also be a trifunctional or higher crosslinking agent having three or more crosslinking reaction groups per molecule. The upper limit of the number of crosslinking reaction groups per molecule is, for example, 5.

[0103] The crosslinking agent (B) is, for example, an isocyanate crosslinking agent. The isocyanate crosslinking agent contains an isocyanate group as a crosslinking reaction group. The isocyanate crosslinking agent (B) can be an aromatic isocyanate compound, an alicyclic isocyanate compound, or an aliphatic isocyanate compound. An isocyanate crosslinking agent (particularly a trifunctional isocyanate crosslinking agent) is preferred from the perspective of durability.

[0104] Examples of aromatic isocyanate compounds that can be used for the crosslinking agent (B) are phenylene diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2′-diphenylmethane diisocyanate, 4,4′-diphenylmethane diisocyanate, 4,4′-toluidine diisocyanate, 4,4′-diphenyl ether diisocyanate, 4,4′-biphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.

[0105] Examples of alicyclic isocyanate compounds that can be used for the crosslinking agent (B) are 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.

[0106] Examples of aliphatic isocyanate compounds that can be used for the crosslinking agent (B) are trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0107] The crosslinking agent (B) may also be a derivative of the above-mentioned isocyanate compound. Examples of the derivatives are polymers (dimers, trimers, pentamers, etc.), adducts obtained by addition with polyols such as trimethylolpropane, urea-modified products, biuret-modified products, allophanate-modified products, isocyanurate-modified products, carbodiimide-modified products, and urethane prepolymers obtained by addition with polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, etc.

[0108] The crosslinking agent (B) is preferably an aromatic isocyanate compound and its derivatives, more preferably toluene diisocyanate and its derivatives (in other words, more preferably toluene diisocyanate (TDI) crosslinking agents). TDI crosslinking agents are superior in reaction uniformity compared to xylylene diisocyanate and its derivatives (in other words, xylylene diisocyanate (XDI) crosslinking agents). Examples of TDI crosslinking agents are adducts of toluene diisocyanate and polyfunctional alcohols, and more specifically trimethylolpropane / toluene diisocyanate trimer adducts.

[0109] As the crosslinking agent (B), commercial products can be used. Examples of commercial products include Millionate MT, Millionate MTL, Millionate MR-200, Millionate MR-400, Coronate L, Coronate HL, and Coronate HX (all manufactured by Tosoh Corporation; all trade names), and Takenate D-102, Takenate D-103, Takenate D-110N, Takenate D-120N, Takenate D-140N, Takenate D-160N, Takenate D-165N, Takenate D-170HN, Takenate D-178N, Takenate 500, and Takenate 600 (all manufactured by Mitsui Chemicals, Inc.; all trade names). As the crosslinking agent (B), Coronate L, Takenate D-102, and Takenate D-103 (all of which are trimethylolpropane / toluene diisocyanate trimer adducts) can be preferably used.

[0110] The isocyanate crosslinking agent can be used alone as one of the above-mentioned isocyanate crosslinking agents, or two or more is used in combination. Relative to 100 parts by weight of the (meth) acrylic polymer (A), the amount of the isocyanate crosslinking agent in the adhesive composition (I) can be, for example, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, 0.5 parts by weight or more, 0.6 parts by weight or more, 1 part by weight or more, 2 parts by weight or more, 2.5 parts by weight or more, 3 parts by weight or more, 5 parts by weight or more, 6 parts by weight or more, 7 parts by weight or more, 8 parts by weight or more, 9 parts by weight or more, 10 parts by weight or more, more than 10 parts by weight, and further can be 11 parts by weight or more. The upper limit of the amount of the compounding is, for example, less than 30 parts by weight, less than 28 parts by weight, less than 25 parts by weight, less than 23 parts by weight, less than 20 parts by weight, less than 19 parts by weight, less than 18 parts by weight, and further can be less than 15 parts by weight.

[0111] The adhesive composition (I) may also include a crosslinking agent other than an isocyanate crosslinking agent. Examples of crosslinking agents other than isocyanate crosslinking agents are peroxide crosslinking agents, epoxy crosslinking agents, imine crosslinking agents, and polyfunctional metal chelates. Relative to 100 parts by weight of (meth) acrylic polymer (A), the amount of the crosslinking agent other than the isocyanate crosslinking agent may be, for example, less than 2 parts by weight, less than 1 part by weight, less than 0.5 parts by weight, less than 0.3 parts by weight, less than 0.28 parts by weight, less than 0.25 parts by weight, less than 0.2 parts by weight, and further may be less than 0.15 parts by weight. The lower limit of the amount of the crosslinking agent is, for example, 0 parts by weight. The crosslinking agent (B) may include an isocyanate crosslinking agent and a peroxide crosslinking agent. From the viewpoint of the durability of the adhesive sheet, the adhesive composition (I) may not substantially include other crosslinking agents, particularly epoxy crosslinking agents.

[0112] [additive]

[0113] The adhesive composition (I) may also contain other additives. Examples of additives are silane coupling agents, polyfunctional alcohols, colorants such as pigments and dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, re-operation enhancers, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, inhibitors, antistatic agents (alkali metal salts, ionic liquids, ionic solids, etc. as ionic compounds), inorganic fillers, organic fillers, powders such as metal powders, particles, and foils. The additives may be formulated in an amount of, for example, less than 10 parts by weight, preferably less than 5 parts by weight, and more preferably less than 1.5 parts by weight relative to 100 parts by weight of the (meth)acrylic polymer (A).

[0114] Examples of the silane coupling agent include epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; amino group-containing silane coupling agents such as 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; (meth)acryl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane.

[0115] When the adhesive composition (I) contains a silane coupling agent, the amount thereof is, for example, 5 parts by weight or less, 3 parts by weight or less, 1 part by weight or less, 0.5 parts by weight or less, 0.2 parts by weight or less, 0.1 parts by weight or less, or further 0.05 parts by weight or less, relative to 100 parts by weight of the (meth)acrylic polymer (A). The adhesive composition (I) may not contain a silane coupling agent.

[0116] The adhesive composition (I) may contain a polyfunctional alcohol. The molecular weight of the polyfunctional alcohol is, for example, 240 or less, 230 or less, 220 or less, 210 or less, 200 or less, 190 or less, 180 or less, 170 or less, 160 or less, and further 150 or less. The lower limit of the molecular weight is, for example, 60 or more, 80 or more, 90 or more, and further 100 or more.

[0117] Examples of the polyfunctional alcohol include alkylene glycols such as ethylene glycol and propylene glycol and polymers thereof; ether glycols such as diethylene glycol and polymers thereof; trimethylolethane; trimethylolpropane; glycerol; and sugar alcohols such as pentaerythritol and sorbitol. The polyfunctional alcohol is preferably trimethylolpropane, glycerol, and diethylene glycol and polymers thereof, and more preferably trimethylolpropane.

[0118] The polyfunctional alcohol may be trifunctional or higher. Examples of trifunctional polyfunctional alcohols are trimethylolpropane and glycerol.

[0119] The polyfunctional alcohol may not have any reactive group other than a hydroxyl group that is reactive with the crosslinking agent (B). The reactive group is, for example, at least one selected from an amino group, a carboxyl group, and an epoxy group, particularly an amino group.

[0120] The amount of the polyfunctional alcohol in the adhesive composition (I) is, for example, 0.5 parts by weight or more and 20 parts by weight or less relative to 100 parts by weight of the (meth)acrylic polymer (A). The upper limit of the amount may be 15 parts by weight or less, 10 parts by weight or less, 8 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, and further may be 3 parts by weight or less.

[0121] The adhesive composition (I) may not contain a crosslinking accelerator such as a catalyst. An example of a crosslinking accelerator is a polyether, polyether polyol, or phosphoric acid ester having a reactive group reactive with the crosslinking agent (B). The reactive group is, for example, at least one selected from a hydroxyl group, an amino group, a carboxyl group, and an epoxy group, in particular a hydroxyl group or an amino group. The adhesive composition (I) may not contain a polyether polyol having an amino group, and may not contain a phosphoric acid ester having a hydroxyl group.

[0122] The type of adhesive composition (I) is, for example, an emulsion type, a solvent type (solution type), an active energy ray curable type (photocurable type), a hot melt type (hot melt type). From the viewpoint of being able to form an adhesive sheet with better durability, the adhesive composition (I) may be a solvent type. The solvent type adhesive composition (I) may not contain a photocuring agent such as an ultraviolet curing agent.

[0123] [Methods for producing the first and second adhesive sheets]

[0124] The first adhesive sheet 2 and the second adhesive sheet 4 are formed from an adhesive composition (I). The first adhesive sheet 2 and the second adhesive sheet 4, for example, contain a crosslinked product of a (meth)acrylic polymer (A). The first adhesive sheet 2 and the second adhesive sheet 4 can be formed from the adhesive composition (I) by the following method. Hereinafter, a method for forming the first adhesive sheet 2 from the adhesive composition (I) is described, and the second adhesive sheet 4 can be formed by the same method.

[0125] The method for producing the first pressure-sensitive adhesive sheet 2 includes, for example, applying a pressure-sensitive adhesive composition (I) including a (meth)acrylic polymer (A) and a crosslinking agent to a substrate to form a coating film; and drying the obtained coating film.

[0126] As a substrate, for example, a release film can be used. The first adhesive sheet 2 formed on the release film can be transferred to an optical film, etc. The substrate can be an optical film. In this case, the first adhesive sheet can be formed on the optical film, so that an optical film with the first adhesive sheet can be obtained.

[0127] The release film can be used as a separator after the first adhesive sheet 2 is transferred to the optical film until the first adhesive sheet 2 is actually used, and the process can be simplified.

[0128] Examples of the constituent material of the release film include plastic films, porous materials such as paper, cloth, and nonwoven fabrics, nets, foam sheets, metal foils, and appropriate thin sheets such as laminates thereof. Plastic films are preferably used because of their excellent surface smoothness.

[0129] The plastic film is not particularly limited, and examples thereof include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.

[0130] The thickness of the release film is usually 5 to 200 μm, preferably about 5 to 100 μm. The release film may be subjected to release treatments such as silicone, fluorine, and long-chain alkyl. The release film may also be subjected to release and antifouling treatments using fatty acid amide-based release agents, silica powder, and the like, or antistatic treatments such as coating-type, mixing-type, and vapor deposition-type.

[0131] A solution (adhesive solution) containing the adhesive composition (I) may also be applied to the substrate. The solid content concentration of the adhesive solution is, for example, 5 to 50% by weight, preferably 10 to 40% by weight. It should be noted that the adhesive solution can be prepared by appropriately adding a solvent that is the same as or different from the polymerization solvent to the adhesive composition (I) in accordance with the polymerization method of the (meth)acrylic polymer (A).

[0132] As a method for applying the adhesive composition (I) to the substrate, various methods can be used, for example, roll coating, licking roll coating, gravure coating, reverse coating, roller brushing, spraying, dip roll coating, rod coating, blade coating, air knife coating, curtain coating, die lip coating, extrusion coating using a die coater, etc. The amount of the adhesive composition (I) applied can be appropriately adjusted according to the target thickness of the first adhesive sheet 2.

[0133] By drying the coating film, the coating film is cured to form the first adhesive sheet 2. The drying temperature of the coating film is not particularly limited, for example, it is 130°C or less, preferably 125°C or less, more preferably 120°C or less, further preferably 110°C or less, and particularly preferably 100°C or less. The drying temperature of the coating film may be 60°C or more, or 80°C or more. When the drying temperature is 60°C or more, there is a tendency that, for example, the reaction of the isocyanate crosslinking agent proceeds smoothly, the cohesive force of the first adhesive sheet 2 can be increased, and the display unevenness of the image display device can be reduced. When the drying temperature is 130°C or less, there is a tendency that, for example, the reaction rate of the isocyanate crosslinking agent can be appropriately adjusted and transparency can be ensured.

[0134] The drying time of the coating film can be appropriately adjusted according to the composition of the adhesive composition (I), and is preferably 30 to 300 seconds, more preferably 40 to 240 seconds, and particularly preferably 60 to 180 seconds.

[0135] [Optical film]

[0136] The first optical film 1 has main surfaces 1a and 1b facing each other. The main surface 1a is exposed, for example, outside the optical laminate 10A. The main surface 1b faces the first adhesive sheet 2. The surface of the first optical film 1 on which the first adhesive sheet 2 is laminated, that is, the main surface 1b of the first optical film 1, can be subjected to a surface modification treatment. According to the main surface 1b subjected to the surface modification treatment, the adhesion between the first optical film 1 and the first adhesive sheet 2 can be further improved. The surface modification treatment can appropriately utilize the surface modification treatment described above for the first adhesive sheet 2. The main surface 1b can be subjected to a corona treatment as a surface modification treatment. When the main surface 1b is subjected to a corona treatment, conditions such as the discharge amount can be appropriately adjusted within the range described above for the first adhesive sheet 2, for example.

[0137] The second optical film 3 has main surfaces 3a and 3b facing each other. The main surface 3a faces the first adhesive sheet 2. The main surface 3a is the surface of the second optical film 3 on which the first adhesive sheet 2 is laminated. The main surface 3b faces the second adhesive sheet 4. The main surface 3b is the surface of the second optical film 3 on which the second adhesive sheet 4 is laminated. The main surfaces 3a and 3b may be subjected to surface modification. By subjecting the main surface 3a to surface modification, the above-mentioned adhesion F can be further improved. By subjecting the main surface 3b to surface modification, the adhesion between the second optical film 3 and the second adhesive sheet 4 can be further improved. The surface modification may be applied to at least a portion of the main surfaces 3a and 3b of the second optical film 3. The surface modification may be applied only to the ends of the main surfaces 3a and 3b of the second optical film 3, or may be applied to the entire main surfaces 3a and 3b. The surface modification may appropriately utilize the surface modification described above for the first adhesive sheet 2. The main surfaces 3a and 3b may be subjected to corona treatment as the surface modification. When the main surfaces 3 a and 3 b are subjected to corona treatment, conditions such as the amount of discharge can be appropriately adjusted within the range described above for the first pressure-sensitive adhesive sheet 2 , for example.

[0138] The first optical film 1 and the second optical film 3, for example, include at least one selected from a polarizing film and a phase difference film. The first optical film 1 may include a polarizing film. The second optical film 3 may include a phase difference film. The first optical film 1 and the second optical film 3 may also be a laminated film including a polarizing film and / or a phase difference film. The first optical film 1 and the second optical film 3 may also include a film made of glass.

[0139] The polarizing film includes a polarizer. The polarizing film typically includes a polarizer and a protective film (transparent protective film). The protective film is, for example, arranged in contact with the main surface of the polarizer. The polarizer can be arranged between two protective films. The protective film can be arranged on at least one side of the polarizer.

[0140] The polarizer is not particularly limited, and examples thereof include films obtained by adsorbing dichroic substances such as iodine and dichroic dyes on hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified films of ethylene-vinyl acetate copolymers and then uniaxially stretching them; polyene oriented films such as dehydrated products of polyvinyl alcohol and dehydrochlorinated products of polyvinyl chloride, etc. The polarizer is typically formed of a polyvinyl alcohol film (polyvinyl alcohol films include partially saponified films of ethylene-vinyl acetate copolymers) and dichroic substances such as iodine.

[0141] The thickness of the polarizer is not particularly limited, for example, it is 80 μm or less, it can be 50 μm or less, 30 μm or less, 25 μm or less, and further can be 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, for example, it is 1 μm or more, it can be 5 μm or more, 10 μm or more, and further can be 15 μm or more. The dimensional change of the thin polarizer (for example, the thickness is 20 μm or less) is suppressed, which can contribute to the durability of the optical laminate, especially the durability at high temperature.

[0142] As the material of the protective film, a thermoplastic resin with excellent transparency, mechanical strength, thermal stability, moisture barrier, isotropy, etc. can be used. As specific examples of such thermoplastic resins, cellulose resins such as cellulose triacetate, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth) acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof can be cited. The material of the protective film can be a thermosetting resin or ultraviolet curing resin such as (meth) acrylic acid, carbamate, acrylic carbamate, epoxy, silicone, etc. In the case where the polarizing film has two protective films, the materials of the two protective films can be the same or different. For example, a protective film composed of a thermoplastic resin can be attached to one main surface of the polarizer by an adhesive, and a protective film composed of a thermosetting resin or an ultraviolet curing resin can be attached to the other main surface of the polarizer. The protective film can contain one or more arbitrary additives. Examples of the additive include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.

[0143] It should be noted that the film containing (meth) acrylic resin has a tendency to have a low bonding strength with the adhesive sheet. However, in the present embodiment, by subjecting the principal surface 3a of the second optical film 3 to surface modification treatment, even when the surface of the protective film containing (meth) acrylic resin is equivalent to the principal surface 3a of the second optical film 3, the above-mentioned adhesion F can be adjusted to a sufficiently high value.

[0144] The thickness of the protective film can be appropriately determined, but is generally about 10 to 200 μm in consideration of strength, handling properties such as ease of handling, and thin film properties.

[0145] The polarizer and the protective film are usually bonded together via a water-based adhesive or the like. Examples of the water-based adhesive include isocyanate adhesives, polyvinyl alcohol adhesives, gelatin adhesives, vinyl latex, water-based polyurethane, and water-based polyester. Examples of adhesives other than the above-mentioned adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Electron beam curing polarizing film adhesives show appropriate adhesion to various protective films. The adhesive may also contain a metal compound filler.

[0146] In the polarizing film, a retardation film or the like may be formed on the polarizer instead of the protective film, and another protective film or a retardation film or the like may be further provided on the protective film.

[0147] The protective film may be provided with a hard coat layer on the surface of the protective film opposite to the surface to which the polarizer is bonded, or may be subjected to treatment for the purpose of anti-reflection, anti-sticking, diffusion, anti-glare, etc.

[0148] The polarizing film may be a circular polarizing film.

[0149] As the retardation film, a film obtained by stretching a polymer film or a film obtained by orienting and fixing a liquid crystal material can be used. The retardation film has birefringence in the plane and / or in the thickness direction, for example.

[0150] Examples of the phase difference film include anti-reflection phase difference films (see Japanese Patent Application Publication No. 2012-133303

[0221] ,

[0222] , and

[0228] ), viewing angle compensation phase difference films (see Japanese Patent Application Publication No. 2012-133303

[0225] and

[0226] ), and tilted orientation phase difference films for viewing angle compensation (see Japanese Patent Application Publication No. 2012-133303

[0227] ).

[0151] The retardation film is not particularly limited in terms of, for example, retardation value, arrangement angle, three-dimensional birefringence, single layer or multilayer, etc., as long as it substantially has the above-mentioned function, and a known retardation film can be used.

[0152] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, and particularly preferably 3 to 8 μm.

[0153] The retardation film is composed of two layers, for example, a quarter-wave plate and a half-wave plate, which are obtained by aligning and fixing a liquid crystal material.

[0154] Figure 2 This is a schematic cross-sectional view showing another example of the optical layered body. Figure 2 The optical laminate 10B has a laminated structure in which the second adhesive sheet 4 , the retardation film 3A, the first adhesive sheet 2 , the polarizing film 1A, and the protective film 5 are laminated in this order.

[0155] The protective film 5 has the function of protecting the polarizing film 1A as the outermost layer during the circulation and storage of the optical laminate 10B, and when the optical laminate 10B is introduced into the image display device. In addition, the protective film 5 can be a protective film that functions as a window to the external space when it is introduced into the image display device. The protective film 5 is typically a resin film. The resin constituting the protective film 5 is, for example, polyester such as PET, polyolefins such as polyethylene and polypropylene, acrylic acid, cycloolefins, polyimides and polyamides, preferably polyesters. However, it should be noted that the protective film 5 is not limited to the above examples, and the protective film 5 can also be a glass film or a laminated film including a glass film. The protective film 5 can be subjected to surface treatments such as anti-glare, anti-reflection, and antistatic.

[0156] The protective film 5 may be bonded to the polarizing film 1A by any adhesive. The bonding may be achieved by using the first adhesive sheet 2 or the second adhesive sheet 4 .

[0157] The optical layered body may have any configuration as long as it includes a pressure-sensitive adhesive sheet formed by the above-mentioned method for producing a pressure-sensitive adhesive sheet.

[0158] The optical laminate of the present embodiment is typically used in an image display device. The image display device is, for example, an EL display such as a liquid crystal display, an organic EL display, and an inorganic EL display.

[0159] [Shape of the Second Adhesive Sheet]

[0160] At least a portion of the end of the second adhesive sheet 4 may be located further inward than the side of the second optical film 3. This allows the tip of the knife of the reoperation tool to more easily cut between the second adhesive sheet 4 and the adherend. As a result, the reoperability can be further improved.

[0161] Figure 3 Schematic cross-sectional view showing an example of an optical laminate with a substrate. Figure 3As shown, the optical laminate 11A with a substrate includes an optical laminate 10C and a substrate 8. Specifically, the optical laminate 11A with a substrate has a structure in which a first optical film 1, a first adhesive sheet 2, a second optical film 3, a second adhesive sheet 4A, and a substrate 8 are sequentially laminated. As the substrate 8, for example, a release film can be used. The substrate 8 can be an optical film or an image forming layer 6 described later. For example, the substrate 8 can be used as a separator in the optical laminate 10C until the second adhesive sheet 4 is actually used.

[0162] As the constituent material of the release film used for the substrate 8, for example, there can be mentioned: plastic films such as polyethylene, polypropylene, polyethylene terephthalate, polyester films, porous materials such as paper, cloth, non-woven fabrics, nets, foam sheets, metal foils and their laminates, etc., and suitable thin sheets, etc. are preferably used in view of excellent surface smoothness.

[0163] The plastic film is not particularly limited as long as it is a film that can protect the second adhesive sheet 4A, and examples thereof include polyethylene films, polypropylene films, polybutylene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.

[0164] The thickness of the release film that can be used for the substrate 8 is usually 5 to 200 μm, preferably about 5 to 100 μm. If necessary, the release film may be subjected to release and antifouling treatment using silicone, fluorine, long-chain alkyl or fatty acid amide release agents, silica powder, etc., or antistatic treatment such as coating, mixing, and vapor deposition. In particular, by appropriately subjecting the surface of the release film to release treatment such as silicone treatment, long-chain alkyl treatment, and fluorine treatment, the releasability from the second adhesive sheet 4A can be further improved.

[0165] In addition, the release film used when producing the second pressure-sensitive adhesive sheet 4A can be used as the base material 8 .

[0166] In the optical laminate 10C, the second adhesive sheet 4A is formed on a portion of a main surface 3b of the second optical film 3. The area of ​​the main surface of the second adhesive sheet 4A may be smaller than the area of ​​the main surface 3b of the second optical film 3. That is, the optical laminate 11A with a substrate may have a given distance between the end of the second adhesive sheet 4A and the side of the second optical film 3. In the direction orthogonal to the stacking direction of the optical laminate 10C, the end of the second adhesive sheet 4A may be entirely located inside. That is, in the direction orthogonal to the stacking direction of the optical laminate 10C, the side 4s of the second adhesive sheet 4A may be entirely located closer to the inside than the side 11a of the optical laminate 11A with a substrate.

[0167] As a method for setting the second adhesive sheet 4A in the optical laminate 11A with a substrate so that the end of the second adhesive sheet 4A is located closer to the inside than the side 11a of the optical laminate 11A with a substrate, there can be cited: (i) a method of designing the second adhesive sheet 4A in a manner of forming a given amount of the portion closer to the inside than the end of the punched optical film during coating or transfer; and (ii) a method of coating the adhesive composition (I) for forming the second adhesive sheet 4A to form an adhesive sheet, and then removing a part of the adhesive sheet. Alternatively, the optical laminate 11A with a substrate can also be prepared by (iii) forming an adhesive sheet on a substrate such as a release film having a smaller area of ​​the main surface than the second optical film 3 to prepare an adhesive sheet with a substrate, and bonding the adhesive sheet with a substrate to the second optical film 3.

[0168] In the optical laminate 11A with a substrate, another example of a method of arranging the second adhesive sheet 4A in such a manner that the end of the second adhesive sheet 4A is located closer to the inside than the side 11a of the optical laminate 11A with a substrate is (iv) a method utilizing end treatment. In the method utilizing end treatment, first, the optical laminate with a substrate is pressurized from its stacking direction. As for pressurization, for example, clamps such as clamps are used to pressurize from both sides of the optical laminate with a substrate. Alternatively, the optical laminate with a substrate can be pressurized in the stacking direction by fixing one side of the optical laminate with a substrate and pressurizing from the other side. By pressurizing the optical laminate with a substrate, the end of the adhesive sheet can be made to protrude from the end edge of the optical laminate with a substrate, in detail, from the side of the second optical film. Next, the protruding end of the adhesive sheet is cut or cut. Then, by releasing the pressure applied to the optical laminate with substrate, the second adhesive sheet 4 can be made in a manner that the end of the second adhesive sheet 4A is located closer to the inside than the side of the second optical film 3. It should be noted that in cutting or cutting, only the end of the protruding adhesive sheet can be cut or cut, or the end edge of the optical laminate can be cut or cut together. In the method of end processing, for example, by adjusting the cutting amount or cutting amount, adjusting the pressure applied to the optical laminate with substrate, and / or adjusting the elastic modulus (storage modulus) of the adhesive sheet, the shape of the end of the second adhesive sheet and the distance between the end of the second adhesive sheet and the side of the second optical film can be adjusted.

[0169] In the optical layered body 11A with a substrate, the optical layered body with a substrate is stretched from one side or both sides of the optical layered body with a substrate toward the outside in the thickness direction of the adhesive sheet, so that the end of the second adhesive sheet 4A is located closer to the inside than the side surface 11a of the optical layered body 11A with a substrate. The second adhesive sheet 4A can be manufactured in a manner.

[0170] In the optical laminate 11A with a substrate, at least a portion of the end of the second adhesive sheet 4A can be located further inward than the side surface 11a of the optical laminate 11A with a substrate. The end of the second adhesive sheet 4 located further inward than the side surface 11a of the optical laminate 11A with a substrate can be formed at 1 / 2 or more of the entire circumference of the second optical film 3, or at 3 / 4 or more of the entire circumference.

[0171] Another example of a shape that the end of the second adhesive sheet may have is Figures 4 to 6 shown. Figure 4 2 is a schematic cross-sectional view showing another example of an optical laminate with a substrate. Figure 4 As shown, the optical laminate 11B with a substrate includes an optical laminate 10D and a substrate 8. The optical laminate 11B with a substrate has a structure in which the substrate 8 is laminated on the second adhesive sheet 4B of the optical laminate 10D. In the optical laminate 11B with a substrate, when viewed from a direction orthogonal to the lamination direction of the optical laminate 10D, the end of the second adhesive sheet 4B has a curved surface 4t that is curved inwardly convex.

[0172] Figure 5 2 is a schematic cross-sectional view showing another example of an optical laminate with a substrate. Figure 5 As shown, the optical laminate 11C with a substrate includes an optical laminate 10E and a substrate 8. The optical laminate 11C with a substrate has a structure in which the substrate 8 is laminated on the second adhesive sheet 4C of the optical laminate 10E. The length of the second adhesive sheet 4C in the direction orthogonal to the lamination direction of the optical laminate 10E increases as it moves from the second optical film 3 toward the substrate 8. That is, in the direction orthogonal to the lamination direction of the optical laminate 10E, the distance between the side surface 11c of the optical laminate 11C with a substrate and the side surface 4u of the second adhesive sheet 4C decreases as it moves from the second optical film 3 toward the substrate 8.

[0173] Figure 6 2 is a schematic cross-sectional view showing another example of an optical laminate with a substrate. Figure 6 As shown, the optical laminate 11D with a substrate includes an optical laminate 10F and a substrate 8. The optical laminate 11D with a substrate has a structure in which the substrate 8 is laminated on the second adhesive sheet 4D of the optical laminate 10F. The length of the second adhesive sheet 4D in the direction orthogonal to the lamination direction of the optical laminate 10F decreases as it moves from the second optical film 3 toward the substrate 8. That is, in the direction orthogonal to the lamination direction of the optical laminate 10F, the distance between the side 11d of the optical laminate 11D with a substrate and the side 4v of the second adhesive sheet 4D increases as it moves from the second optical film 3 toward the substrate 8.

[0174] exist Figures 4 to 6In the optical laminate 11B to 11D with a substrate, at least a portion of the end of the second adhesive sheet 4B to 4D may be located at a position closer to the inside than the side surfaces 11b to 11d of the optical laminate 10D to 10F. In the optical laminate 11B to 11D with a substrate, at least a portion of the end of the second adhesive sheet 4B to 4D may be in contact with the side surfaces 11b to 11d of the optical laminate 10D to 10F, or may be located at a position closer to the outside than the side surfaces 11b to 11d of the optical laminate 10D to 10F in a direction orthogonal to the stacking direction of the optical laminate.

[0175] In the direction orthogonal to the stacking direction of the optical laminate, the ends of the first adhesive sheet 2 may be completely located inside. At least a portion of the ends of the first adhesive sheet 2 may be located closer to the inside than the side surface of the second optical film 3. In addition, in these optical laminates 11A to 11D with substrates, the shape of the end of the first adhesive sheet may be the same as or different from the shape of the end of the second adhesive sheet.

[0176] exist Figures 3 to 6 In the embodiment of the present invention, the maximum distance L between the surface of the end of the second adhesive sheet and the side of the second optical film is, for example, 2 μm or more, 4 μm or more, 5 μm or more, and further 7 μm or more. The upper limit of the maximum distance L can be 100 μm, 50 μm, 30 μm, 20 μm, or 15 μm. The maximum distance L refers to the maximum value of the distance between the side of the second adhesive sheet and the side of the second optical film in a direction orthogonal to the stacking direction of the optical laminate. By appropriately adjusting the maximum distance L, reoperability can be further improved. It should be noted that the maximum distance L can be adjusted by, for example, adjusting the thickness T2 of the second adhesive sheet, the storage modulus of the second adhesive sheet, the presence or absence of oligomers contained in the adhesive composition (I), and the pressure when the optical laminate is pressurized.

[0177] [Image display device]

[0178] Figure 7 It is a schematic cross-sectional view showing an example of an image display device. Figure 7 The image display device 20A includes a substrate 7, an image forming layer (e.g., an organic EL layer or a liquid crystal layer) 6, and an optical laminate 10A. Specifically, the image display device 20A has a laminated structure in which the substrate 7, the image forming layer 6, the second adhesive sheet 4, the second optical film 3, the first adhesive sheet 2, and the first optical film 1 are laminated in this order. The image display device 20A may also include Figure 2~Figure 6 The optical layered bodies 10B to 10F described in hereinafter may be used in place of the optical layered body 10A. The substrate 7 and the image forming layer 6 may have the same configurations as those of a substrate and an image forming layer included in a known image display device.

[0179] Figure 7 The image display device 20A may be an organic EL display or a liquid crystal display. However, the image display device 11 is not limited to this example, and the image display device 11 may be an electroluminescent (EL) display, a plasma display (PD), a field emission display (FED), etc. The image display device 11 may also be used for home appliances, vehicles, public information displays (PID), etc.

[0180] The image display device may have any configuration as long as it includes the pressure-sensitive adhesive sheet and / or the optical layered body described above.

[0181] The image display device may be a narrow-frame image display device. An example of such an image display device is shown in Figure 8 . Figure 8 It is a cross-sectional view schematically showing another example of the image display device. Figure 8 The image display device 20B has a laminated structure in which a substrate 7, an image forming layer 6, and an optical laminate 10A are laminated in this order. Specifically, the image display device 20B has a laminated structure in which a substrate 7, an image forming layer 6, a second adhesive sheet 4, a second optical film 3, a first adhesive sheet 2, and a first optical film 1 are laminated in this order. Figure 8 As shown in FIG. 1 , the image display device 20B has the same configuration as the image display device 20A except that a distance W is provided between the side surface of the image forming layer 6 and the side surface of the optical laminate 10A. The image display device 20B may also have Figure 2~Figure 6 The optical layered bodies 10B to 10F described in the specification are used instead of the optical layered body 10A.

[0182] In the image display device 20B, the distance W between the side 6s of the image forming layer 6 and the side 10s of the optical laminate 10A is, for example, 5.0 mm or less, and can be 3.0 mm or less, 2.0 mm or less, 1.0 mm or less, 0.7 mm or less, 0.5 mm or less, 0.3 mm or less, 0.2 mm or less, and can further be 0.1 mm or less. The lower limit of the distance W is, for example, 0 mm. According to the image display device of this embodiment, since the image display device 20B has the optical laminate 10A, the optical laminate 10A can be peeled off from the image forming layer 6 even in the case of a narrow frame.

[0183] [Method for peeling optical laminate]

[0184] Next, a method for peeling the optical layered body from the image forming layer in the image display device will be described.

[0185] As described above, the image display device 20A has, for example, a structure in which the optical laminate 10A is laminated on the image forming layer 6. In the image display device 20A, peeling the optical laminate 10A from the image forming layer 6 includes, for example: (i) making a starting point; and (ii) peeling the optical laminate 10A from the image forming layer 6 by stretching the starting point by hand.

[0186] In the step (i), the starting point is produced, for example, by peeling off the end of the optical laminate 10A between the first adhesive sheet 2 and the second optical film 3 in the optical laminate 10A. The starting point is produced, for example, by inserting the tip of a knife of a re-operating tool such as a cutter and a scraper between the first adhesive sheet 2 and the second optical film 3.

[0187] The image display device having the starting point thus created is shown in Fig. 9 . Fig. 9 is a schematic cross-sectional view showing an example of an image display device after the starting point is produced. Fig. 9 As shown, in the image display device 20C, the end of the first adhesive sheet 2 is peeled from the second optical film 3 to form a starting point 30a. The starting point 30a includes, for example, the end of the first optical film 1 and the end of the first adhesive sheet 2.

[0188] The production of the starting point can be carried out at room temperature or in a state where the image display device 20C is heated. The heating temperature of the image display device 20C is not limited to a specific temperature, and is, for example, 70° C. to 100° C. The heating time of the image display device 20C is not limited to a specific time, and is, for example, 1 second to 30 seconds. The heating of the image display device 20C is carried out, for example, by placing the image display device 20C on a hot plate.

[0189] In the step (ii), the optical laminate 10A is peeled off from the image forming layer 6. The peeling of the optical laminate 10A from the image forming layer 6 is carried out, for example, in a heated state. That is, the optical laminate 10A is peeled off from the image forming layer 6 while the image display device 20C is placed on a hot plate. While holding the starting point 30a, for example, the starting point 30a is stretched at an angle of 180° relative to the image forming layer 6, thereby allowing the optical laminate 10A to be peeled off from the image forming layer 6. In the step (ii), the heating temperature of the image display device 20C is not limited to a specific temperature, and is, for example, 70°C to 100°C.

[0190] It should be noted that, with respect to the image display device 20C, Fig. 9In the above, a method of peeling the optical laminate from the image forming layer is described for the image display device 20C in which the optical laminate 10A is laminated on the image forming layer 6 , but the same method can also be applied to image display devices in which the optical laminates 10B to 10F are laminated.

[0191] Example

[0192] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the examples shown below.

[0193] The correspondence between the abbreviations or names shown in the following description and the compounds is as follows.

[0194] BA: n-butyl acrylate

[0195] BzA: Benzyl acrylate

[0196] PEA: Phenoxyethyl acrylate

[0197] AA: Acrylic acid

[0198] HBA: 4-Hydroxybutyl Acrylate

[0199] ACMO: N-acryloylmorpholine

[0200] AIBN: 2,2'-azobisisobutyronitrile

[0201] C / L: trimethylolpropane / toluene diisocyanate trimer adduct (isocyanate crosslinking agent, manufactured by Tosoh Corporation, CORONATE L)

[0202] Peroxide: Benzoyl peroxide (Nyper BMT, manufactured by NOF Corporation)

[0203] KBM-403: 3-Glycidoxypropyltrimethoxysilane (a silane coupling agent having an epoxy group at the end, manufactured by Shin-Etsu Chemical Co., Ltd.)

[0204] SAT-10: A polyether compound having a reactive silyl group (manufactured by Kaneka Corporation, Silyl SAT10)

[0205] [Phase difference film R1]

[0206] A polycarbonate resin film (stretched film of a resin film, manufactured by Teijin Limited, PURE-ACERM) was used as the retardation film R1. In addition, both surfaces of the retardation film R1 were previously subjected to a corona treatment.

[0207] [Phase difference film R2]

[0208] The phase difference film R2 was produced as follows.

[0209] (Preparation of the First Phase Difference Film)

[0210] 26.2 parts by weight of isosorbide (ISB), 100.5 parts by weight of 9,9-[4-(2-hydroxyethoxy)phenyl]fluorene (BHEPF), 10.7 parts by weight of 1,4-cyclohexanedimethanol (1,4-CHDM), 105.1 parts by weight of diphenyl carbonate (DPC) and 0.591 parts by weight of cesium carbonate (0.2% by weight aqueous solution) as a catalyst were put into a reaction vessel and dissolved in a nitrogen atmosphere (about 15 minutes). At this time, the heat medium temperature of the reaction vessel was set to 150°C, and stirring was implemented as needed. Next, the pressure in the reaction vessel was reduced to 13.3 kPa, and the heat medium temperature was raised to 190°C in 1 hour. The phenol generated as the heat medium temperature rises is exported to the outside of the reaction vessel (the same below). Next, after the temperature in the reaction container was maintained at 190°C for 15 minutes, the pressure in the reaction container was changed to 6.67 kPa, and the temperature of the heat medium was raised to 230°C in 15 minutes. At the moment when the stirring torque of the stirrer provided in the reaction container increased, it took 8 minutes to raise the temperature of the heat medium to 250°C, and further the pressure in the reaction container was brought to less than 0.200 kPa. After reaching the given stirring torque, the reaction was terminated, and the generated reactants were extruded into water and pelletized. In this way, a polycarbonate resin having a composition of BHEPF / ISB / 1,4-CHDM=47.4 mol% / 37.1 mol% / 15.5 mol% was obtained. The glass transition temperature of the obtained polycarbonate resin was 136.6°C and the reduced viscosity was 0.395 dL / g.

[0211] After the prepared polycarbonate resin pellets were vacuum dried at 80°C for 5 hours, a long resin film with a thickness of 120 μm was obtained using a film-making device equipped with a single screw extruder (manufactured by Isuzu Chemical Industries, Ltd., screw diameter 25 mm, cylinder setting temperature 220°C), a T-die (width 200 mm, setting temperature 220°C), a chill roll (setting temperature 120-130°C) and a winder. Next, the obtained resin film was stretched in the width direction by a tenter stretching machine at a stretching temperature of 137-139°C and a stretching ratio of 2.5 times to obtain a first retardation film.

[0212] (Production of the Second Phase Difference Film)

[0213] 20 parts by weight of a side chain liquid crystal polymer (weight average molecular weight 5000) represented by the following chemical formula (I) (wherein 65 and 35 are the mole % of each structural unit), 80 parts by weight of a polymerizable liquid crystal (manufactured by BASF, trade name "Paliocolor LC242") showing a nematic liquid crystal phase, and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals, trade name "IRGACURE 907") were dissolved in 200 parts by weight of cyclopentanone to prepare a liquid crystal coating liquid. Next, the prepared liquid crystal coating liquid was applied to the surface of a norbornene resin film (manufactured by Zeon Co., Ltd., trade name "ZEONEX") as a substrate film by a wire bar coater, and then heated and dried at 80°C for 4 minutes to orient the liquid crystal contained in the coating film. Next, the coating film was cured by irradiation with ultraviolet rays, and a liquid crystal fixed layer (thickness 0.58 μm) as a second phase difference film was formed on the substrate film. The in-plane phase difference Re of the liquid crystal fixed layer for light of wavelength 550nm is 0nm, and the phase difference Rth in the thickness direction is -71nm (nx=1.5326, ny=1.5326, nz=1.6550). The liquid crystal fixed layer shows the refractive index characteristic of nz>nx=ny.

[0214] [Chemical formula 1]

[0215]

[0216] (Production of Phase Difference Film R2)

[0217] The phase difference film R2 is prepared by bonding one side of the first phase difference film prepared above to the liquid crystal fixing layer of the second phase difference film via an adhesive. It should be noted that in Examples 5A and 5B, the first adhesive sheet, the phase difference film R2 and the second adhesive sheet are stacked together in sequence. That is, in Examples 5A and 5B, the first adhesive sheet, the first phase difference film, the adhesive, the second phase difference film, and the second adhesive sheet are stacked together in sequence. The surface of the first phase difference film stacked with the first adhesive sheet is pre-corona treated. The surface of the second phase difference film stacked with the second adhesive sheet is not corona treated.

[0218] The following describes the evaluation methods for the (meth)acrylic polymer, the first pressure-sensitive adhesive sheet, the second pressure-sensitive adhesive sheet, and the optical laminate produced in Examples and Comparative Examples.

[0219] [Weight average molecular weight (Mw)]

[0220] The weight average molecular weight (Mw) of the (meth)acrylic polymer was evaluated by GPC under the following conditions.

[0221] Analytical equipment: Waters, Acquity APC

[0222] ·Chromatographic column: G7000H manufactured by Tosoh Corporation XL +GMH XL +GMH XL

[0223] Column temperature: 40℃

[0224] Eluent: Tetrahydrofuran (with added acid)

[0225] Flow rate: 0.8 mL / min

[0226] Injection volume: 100μL

[0227] Detector: Differential Refractometer (RI)

[0228] ·Standard sample: Agilent, polystyrene (PS)

[0229] [Storage modulus G A '(23℃)]

[0230] The storage modulus G of the first adhesive sheet at 23°C was measured by the following method: A '(23°C) was evaluated. First, a sample for measurement was prepared. The sample for measurement was a sample obtained by punching a laminated body on which multiple first adhesive sheets were stacked into a disc shape. The diameter of the bottom surface of the sample for measurement was 8 mm, and the thickness of the sample for measurement was 1 mm. Next, a dynamic viscoelasticity measurement was performed on the sample for measurement. The dynamic viscoelasticity measurement used ARES-G2 manufactured by TA Instruments. Based on the results of the dynamic viscoelasticity measurement, the storage modulus G of the first adhesive sheet at 23°C was calculated. A It should be noted that the conditions for the dynamic viscoelasticity measurement are as follows.

[0231] ·Measurement conditions

[0232] Frequency: 1Hz

[0233] Deformation mode: Twist

[0234] Measuring temperature: -70℃~150℃

[0235] Heating speed: 5℃ / min

[0236] [Storage modulus G B '(23℃)]

[0237] The storage modulus G of the second adhesive sheet at 23°C was measured by the following method: B' was evaluated. First, a sample for measurement was prepared. The sample for measurement was a sample obtained by punching a laminated body with a plurality of second adhesive sheets stacked on top of each other into a disc shape. The diameter of the bottom surface of the sample for measurement was 8 mm, and the thickness of the sample for measurement was 1 mm. In addition to using this sample for measurement, by comparing the above-mentioned [storage modulus G A The storage modulus G of the second adhesive sheet at 23°C was obtained in the same way as in '(23°C) B '(23℃).

[0238] [Measurement of Adhesion Force F]

[0239] ·F1(23℃) and F0(23℃)

[0240] The optical laminate with release film of the examples and comparative examples was cut into a size of 25 mm in width and 100 mm in length, the release film was peeled off, and the laminate was fixed to a soda-lime glass plate (S200423, manufactured by Matsunami Glass Co., Ltd.) via a double-sided tape (No. 500, manufactured by Nitto Denko Corporation) to produce an optical laminate with glass A.

[0241] Next, in the optical laminate A with glass, a cutter knife was inserted between the first adhesive sheet and the second optical film (phase difference film) to make a starting point. After making the starting point, the 90° peeling adhesive force was immediately measured. The 90° peeling adhesive force was measured using a tensile testing machine (device name: precision universal testing machine, Autograph AG-IS, manufactured by Shimadzu Corporation) under the conditions of a peeling angle of 90 degrees and a tensile speed of 300 mm / min.

[0242] F1(80℃)

[0243] The optical laminate A with glass was placed on a hot plate set at 80°C for 15 seconds in such a way that the glass side of the optical laminate A with glass was in contact with the hot plate. Then, the knife of the cutter was immediately inserted between the first adhesive sheet and the second optical film (phase difference film) to make a starting point. After making the starting point, the 90° peeling adhesive force was immediately measured. The measuring conditions of the 90° peeling adhesive force are as described above.

[0244] [Measurement of Adhesion Strength G]

[0245] G0(23℃)

[0246] The optical laminate with release film of the embodiment and the comparative example was cut into a size of 25 mm in width and 100 mm in length, the release film was peeled off, and fixed to an alkali-free glass plate (EagleXG manufactured by Corning Incorporated) to produce an optical laminate with glass B. The optical laminate with glass B was placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the second adhesive sheet and the alkali-free glass plate. The optical laminate with glass B was taken out of the autoclave and allowed to stand at 23°C for 20 minutes. Then, the knife of the cutter was immediately inserted between the second adhesive sheet and the alkali-free glass plate to make a starting point. After making the starting point, the 90° peeling adhesion was immediately measured. The conditions for measuring the 90° peeling adhesion are as described above.

[0247] G2 (23°C)

[0248] G2 (23° C.) was measured by the same method as the measurement method of G0 (23° C.) described above, except that the optical layered body B with glass was taken out of the autoclave and left to stand at 23° C. and 55% RH for 2 weeks.

[0249] G0(80℃)

[0250] The optical laminate B with glass was placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the second adhesive sheet and the alkali-free glass plate. The optical laminate B with glass was taken out of the autoclave and allowed to stand at 23°C for 20 minutes. Then, the optical laminate B with glass was immediately allowed to stand on a hot plate set at 80°C for 15 seconds in such a way that the glass side of the optical laminate B with glass was in contact with the hot plate. Then, the knife of the cutter was immediately inserted between the second adhesive sheet and the alkali-free glass plate to make a starting point. After making the starting point, the 90° peel adhesion was immediately measured. The conditions for measuring the 90° peel adhesion are as described above.

[0251] [film thickness]

[0252] The thickness of the first adhesive sheet and the thickness of the second adhesive sheet were measured using a micrometer (manufactured by MITUTOYO CORPORATION).

[0253] [Reoperation success rate after interlayer peeling]

[0254] The reoperability (success rate of reoperation after interlayer peeling) of the optical laminate with glass was evaluated by the following method. First, the knife of the reoperation device was inserted between the first adhesive sheet and the phase difference film of the optical laminate with glass in each embodiment and comparative example, so that interlayer peeling occurs at the end of the optical laminate between the first adhesive sheet and the phase difference film, thereby making a starting point. The starting point includes a first adhesive sheet and a first optical film (polarizing film). Next, the optical laminate with glass is allowed to stand on a hot plate set at 80°C for 15 seconds in such a way that the glass side of the optical laminate with glass is in contact with the hot plate. Then, immediately on the hot plate set at 80°C, while holding the starting point, the starting point is stretched at an angle of 180° relative to the glass, thereby peeling the optical laminate from the glass. At this time, the situation where the optical laminate can be peeled off from the glass without a part of the optical laminate remaining on the glass is evaluated as "successful". The above evaluation was implemented 10 times for each embodiment and comparative example, and the reoperability was evaluated as described below.

[0255] A: The success rate of re-operation after interlayer peeling is 100%

[0256] B: The success rate of re-operation after interlayer peeling is more than 80% and less than 90%

[0257] C: The success rate of re-operation after interlayer peeling is 50% or more and 70% or less

[0258] D: The success rate of re-operation after interlayer peeling is less than 40%

[0259] [End treatment]

[0260] 100 optical laminates with release films of the embodiments and comparative examples were stacked to produce an end-processed laminate. The end-processed laminate was fixed from the top and bottom of the stacking direction of the end-processed laminate using a vise-like clamp. Under a state where the second adhesive sheet was pressed so that it protruded from the end edge of the end-processed laminate, the end-processed laminate was cut together with the second adhesive sheet in a direction orthogonal to the stacking direction of the end-processed laminate, 1.0 mm inside from the end edge of the end-processed laminate, using a rotating knife. In this way, an optical laminate with a release film after the end was processed (hereinafter referred to as "optical laminate after end processing") was produced. In Tables 3 and 4, "Y" indicates that end processing was implemented, and "N" indicates that end processing was not implemented.

[0261] [Preparation of (meth)acrylic polymer A1]

[0262] A monomer mixture containing 79.9 parts by weight of butyl acrylate (BA), 15 parts by weight of benzyl acrylate (BzA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 4-hydroxybutyl acrylate (HBA) was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator was added together with ethyl acetate to 100 parts by weight of the monomer mixture to prepare a reaction solution. After nitrogen replacement was performed while slowly stirring the reaction solution and introducing nitrogen, the liquid temperature in the flask was maintained at around 55°C, and a polymerization reaction was performed for 7 hours. Ethyl acetate was added to the solution after the polymerization reaction, and the solid content concentration was adjusted to 30%, thereby obtaining a solution of (meth)acrylic polymer A1.

[0263] [(Meth)acrylic polymers A2 and A3]

[0264] Solutions of (meth)acrylic polymers A2 and A3 were prepared by the same method as for (meth)acrylic polymer A1, except that the monomers used were changed as shown in Table 1.

[0265]

[0266] [Preparation of Adhesive Compositions B1 to B6]

[0267] Solvent-based adhesive compositions B1 to B6 were obtained by mixing a (meth)acrylic polymer, a crosslinking agent, and an additive to form the composition shown in Table 2. In Table 2, the unit of the amount is parts by mass. In addition, the drying temperature indicates the drying temperature when the adhesive sheet is formed from the adhesive composition.

[0268]

[0269] [Production of Polarizing Film P1]

[0270] In the production of polarizing film P1, first, a polarizer was produced as described below. A long polyvinyl alcohol (PVA) resin film (manufactured by Kuraray Co., Ltd., product name "PE3000", thickness 30μm) was uniaxially stretched along the length direction (total stretching ratio 5.9 times) using a roll stretching machine, and the resin film was subjected to swelling, dyeing, cross-linking, washing and drying treatments in sequence to produce a polarizer with a thickness of 12μm. In the swelling treatment, the resin film was stretched 2.2 times while being treated in pure water at 20°C. In the dyeing treatment, the resin film was stretched 1.4 times while being treated in a 30°C aqueous solution containing iodine and potassium iodide in a weight ratio of 1:7. The iodine concentration in the aqueous solution was adjusted so that the monomer transmittance of the produced polarizer reached 45.0%. The cross-linking treatment adopted a two-stage treatment. In the first stage of cross-linking treatment, the resin film was stretched 1.2 times while being treated in an aqueous solution at 40°C in which boric acid and potassium iodide were dissolved. The content of boric acid in the aqueous solution used in the first stage of cross-linking treatment was set to 5.0% by weight, and the content of potassium iodide was set to 3.0% by weight. In the second stage of cross-linking treatment, the resin film was stretched 1.6 times while being treated in an aqueous solution at 65°C in which boric acid and potassium iodide were dissolved. The content of boric acid in the aqueous solution used in the second stage of cross-linking treatment was set to 4.3% by weight, and the content of potassium iodide was set to 5.0% by weight. A potassium iodide aqueous solution at 20°C was used in the cleaning treatment. The content of potassium iodide in the aqueous solution used in the cleaning treatment was set to 2.6% by weight. The drying treatment was carried out under the drying conditions of 70°C and 5 minutes.

[0271] A triacetyl cellulose (TAC) film (manufactured by Konica Minolta, Ltd., product name "KC2UA", thickness 25 μm) was bonded to each main surface of the polarizer prepared above using a polyvinyl alcohol adhesive. A hard coating layer (thickness 7 μm) was formed on the main surface of the TAC film bonded to one main surface on the side opposite to the polarizer side. In this way, a polarizing film P1 having a structure of a protective layer with a hard coating layer / polarizer / protective layer (without a hard coating layer) was obtained.

[0272] [Production of optical laminate]

[0273] (Example 1)

[0274] The adhesive composition B1 prepared above is applied to the release surface of a 38 μm thick polyethylene terephthalate (PET) film (MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) in such a manner that the thickness of the layer after drying reaches 12 μm, and is dried at 155°C for 1 minute to form a first adhesive sheet on the surface of the release film. The polyethylene terephthalate (PET) film is a release film whose release surface is treated with silicone.

[0275] Next, the first adhesive sheet formed on the surface of the release film was transferred to the polarizing film P1 to produce a polarizing film a with a first adhesive sheet in which the release film, the first adhesive sheet and the polarizing film were stacked in sequence. The release film was peeled off from the polarizing film a with the first adhesive sheet to expose the first adhesive sheet. Then, the surface of the first adhesive sheet on which the polarizing film was not formed was subjected to a corona treatment to produce a polarizing film b with the first adhesive sheet. The corona output was 10 kJ / m 2 .

[0276] Different from the above operation, the adhesive composition B2 prepared above is applied to the release surface of a 38 μm thick polyethylene terephthalate (PET) film (MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) in a manner so that the thickness of the layer after drying reaches 15 μm, and is dried at 155°C for 1 minute to form a second adhesive sheet on the surface of the release film. The polyethylene terephthalate (PET) film is a release film with a silicone treatment on the release surface.

[0277] Next, the second adhesive sheet formed on the surface of the release film was transferred to the phase difference film R1 to produce a phase difference film with a second adhesive sheet a in which the release film, the second adhesive sheet and the phase difference film R1 were sequentially laminated. Before the second adhesive sheet was transferred to the phase difference film R1, the surface of the phase difference film R1 on which the second adhesive sheet was to be formed was subjected to a corona treatment.

[0278] In the retardation film a with the second adhesive sheet, the surface (back surface) of the retardation film R1 without the second adhesive sheet was subjected to corona treatment to prepare a retardation film b with the second adhesive sheet. The corona output was 7 kJ / m 2 .

[0279] Then, the polarizing film b with the first adhesive sheet and the phase difference film b with the second adhesive sheet are combined in such a manner that the polarizing film, the first adhesive sheet, the phase difference film R1, the second adhesive sheet and the release film are stacked in sequence to produce an optical laminate with a release film. Then, the release film is peeled off from the optical laminate with the release film to obtain the optical laminate of Example 1 in which the second adhesive sheet is exposed. Then, glass (alkali-free glass plate, manufactured by Corning Co., Ltd., EAGLE XG) is laminated on the surface of the unlaminated phase difference film R1 of the second adhesive sheet. The second adhesive sheet is bonded to the glass by reciprocating a 2kg roller once. Next, the optical laminate bonded with glass is placed in an autoclave at 50°C and 5 atmospheres (absolute pressure) for 15 minutes to homogenize the bonding between the second adhesive sheet 4 and the alkali-free glass. In this way, an optical laminate with glass of Example 1 is produced. In addition, in the optical laminated body with glass of Example 1, the distance between the side surface of glass and the side surface of the retardation film was within 0.5 mm.

[0280] (Examples 2 to 8, and Comparative Examples 1 to 11)

[0281] The first adhesive sheet, the phase difference film, and the second adhesive sheet described in the following Tables 3 and 4 were used to prepare the optical laminate with glass of each example and comparative example by the same method as in Example 1. However, it should be noted that in Comparative Examples 1 to 11, the surface of the first adhesive sheet on which the polarizing film was not formed was not subjected to corona treatment. The optical laminates prepared in Comparative Examples 1 to 8 had the same structure as the optical laminates prepared in Examples 1 to 8 except that the surface of the first adhesive sheet on which the phase difference film was not formed was not subjected to corona treatment.

[0282] In the calculation of F1(23°C) / F0(23°C) described in Table 7, in Example 1, F1(23°C) used the value of Example 1, and F0(23°C) used the value of Comparative Example 1. The same applies to Examples 2 and thereafter.

[0283] In Tables 7 and 8, "Reoperation" indicates the evaluation result of the above-mentioned [success rate of reoperation after interlayer peeling].

[0284]

[0285]

[0286]

[0287]

[0288]

[0289]

[0290] As shown in Tables 7 and 8, in each example, an optical laminate having improved reoperability compared to the comparative example was obtained. In addition, in each example, after the optical laminate was peeled off from the glass, the phase difference film and the polarizing film did not break. In contrast, in each comparative example, after the optical laminate was peeled off from the glass, the phase difference film and the polarizing film broke.

[0291] Industrial Applicability

[0292] The optical layered body of the present invention can be used in, for example, an image display device.

Claims

1. An optical laminate, wherein a first optical film, a first adhesive sheet, a second optical film and a second adhesive sheet are laminated in this order, The surface of the first adhesive sheet on which the second optical film is laminated has been subjected to surface modification treatment. When the adhesion between the first adhesive sheet and the second optical film at 80°C is defined as F1 (80°C), and the initial adhesion between the second adhesive sheet and the alkali-free glass at 80°C when the second adhesive sheet is bonded to the alkali-free glass is defined as G0 (80°C), the following formula (1) is satisfied: F1(80℃) / G0(80℃)≥2 (1).

2. The optical layered body according to claim 1, wherein: When the adhesion between the first adhesive sheet and the second optical film at 23°C is defined as F1 (23°C), and when the surface of the first adhesive sheet on which the second optical film is laminated is not subjected to surface modification treatment, the adhesion between the first adhesive sheet and the second optical film at 23°C is defined as F0 (23°C), the following formula (2) is satisfied: F1(23℃) / F0(23℃)>1.30 (2).

3. The optical layered body according to claim 1, wherein: The surface modification treatment is corona treatment.

4. The optical laminate according to claim 1, wherein: When the adhesion between the first adhesive sheet and the second optical film at 23°C is defined as F1 (23°C), and the initial adhesion between the second adhesive sheet and the alkali-free glass at 23°C when the second adhesive sheet is bonded to the alkali-free glass is defined as G0 (23°C), the following formula (3) is satisfied: F1(23℃) / G0(23℃)≥1.2 (3).

5. The optical layered body according to claim 1, wherein: The thickness T2 of the second adhesive sheet is 8 μm or more.

6. The optical layered body according to claim 1, wherein: A thickness T2 of the second adhesive sheet and a thickness T1 of the first adhesive sheet satisfy T2 / T1≥1.

1.

7. The optical layered body according to claim 1, wherein: The storage modulus G of the first adhesive sheet at 23°C A '(23°C) and the storage modulus G of the second adhesive sheet at 23°C B '(23℃) satisfies G A '(23℃) / G B '(23℃)≥1.

1.

8. The optical layered body according to claim 1, wherein: When the second adhesive sheet is bonded to the alkali-free glass, the initial bonding strength between the second adhesive sheet and the alkali-free glass at 23°C is defined as G0 (23°C); when the second adhesive sheet is bonded to the alkali-free glass and the bonding strength between the second adhesive sheet and the alkali-free glass at 23°C after 2 weeks at 23°C is defined as G2 (23°C), G2 (23°C) / G0 (23°C) ≤ 1.5 is satisfied.

9. An image display device comprising: The optical layered body according to any one of claims 1 to 8, and Image forming layer.

Citation Information

Patent Citations

  • Acrylic adhesives and its production method

    JP2002069411A

  • Method for sticking adhesive layer

    JP2005213314A

  • Optical display device having polarizing film

    JP2012133303A